2020
DOI: 10.1111/acel.13225
|View full text |Cite
|
Sign up to set email alerts
|

Neuron‐specific deletion of CuZnSOD leads to an advanced sarcopenic phenotype in older mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 47 publications
2
31
2
Order By: Relevance
“…These results further support the feasibility of using in vivo redox status assessment in the development of pathological processes such as sarcopenia. Bhaskaran et al 81 . found that neuron‐specific deletion of CuZnSOD was enough to cause the loss of motor neurons in young mice, but damage to neuromuscular junctions, muscle atrophy, and weakness were not obvious until middle age.…”
Section: Classification Of Mouse Models Of Sarcopeniamentioning
confidence: 99%
“…These results further support the feasibility of using in vivo redox status assessment in the development of pathological processes such as sarcopenia. Bhaskaran et al 81 . found that neuron‐specific deletion of CuZnSOD was enough to cause the loss of motor neurons in young mice, but damage to neuromuscular junctions, muscle atrophy, and weakness were not obvious until middle age.…”
Section: Classification Of Mouse Models Of Sarcopeniamentioning
confidence: 99%
“…The disintegration of the neuromuscular junction (NMJ) is a central focal point in the multifactorial etiology of sarcopenia [ 9 ]. We have previously shown that NMJ disintegration can trigger muscle atrophy and weakness in ageing, and conditions associated with increased oxidative stress [ 10 ]. Notably, the muscle shows reduced oxidative capacity, fiber-type grouping, and signs of denervation.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that Sod1KO mice will develop cardiac dysfunction with age. Age-dependent phenotypic manifestation has been reported in this model [ 27 ]. It is interesting to note that deficiency of MnSOD, a superoxide scavenger expressed in mitochondria, has a greater impact on cardiac dysfunction and pathology compared with CnZnSOD.…”
Section: Discussionmentioning
confidence: 88%